2009
DOI: 10.1186/1471-230x-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer activity of fluvoxamine in rats and its effect on oxidant and antioxidant parameters in stomach tissue

Abstract: BackgroundAlthough many drugs are available for the treatment of gastric ulcers, often these drugs are ineffective. Many antidepressant drugs have been shown to have antiulcer activity in various models of experimental ulcer. One such drug, the antidepressant mirtazapine, has been reported to have an antiulcer effect that involves an increase in antioxidant, and a decrease in oxidant, parameters. To date, however, there is no information available regarding the antiulcer activity for a similar antidepressant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 55 publications
8
42
2
2
Order By: Relevance
“…This result showed that E. prostratahas gastroprotective effect. Our results coinside with may other studies [33][34][35] . In addition to ulcer parameters different types of biochemical parameters or oxidative health biomarkers were also determined in the present study including total oxidant status, malondialdehyde, total antioxidant capacity and CAT were also determined in the current study.…”
Section: Discussioncontrasting
confidence: 53%
“…This result showed that E. prostratahas gastroprotective effect. Our results coinside with may other studies [33][34][35] . In addition to ulcer parameters different types of biochemical parameters or oxidative health biomarkers were also determined in the present study including total oxidant status, malondialdehyde, total antioxidant capacity and CAT were also determined in the current study.…”
Section: Discussioncontrasting
confidence: 53%
“…Although reports have demonstrated that SSRI are associated with increased gastrointestinal bleeding (Dalton et al 2003), many anti-depressant drugs, including SSRI, have been shown to impart anti-ulcer activity in various models of experimental ulcer (Dursun et al 2009;Ji et al 2012). In the study here, pretreatment with fluoxetine significantly prevented mucosal ulcerations induced by INDO and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption was measured at 412 nm using a spectrophotometer. The GSH levels in the gastric mucosa were expressed as nmol/mg tissue [18].…”
Section: Measurement Of Gastric Enzyme Activitymentioning
confidence: 99%